2018
DOI: 10.1111/cch.12579
|View full text |Cite
|
Sign up to set email alerts
|

“If I had been given that information back then”: An interpretive description exploring the information needs of adults with cerebral palsy looking back on their transition to adulthood

Abstract: Clinicians assisting young people with CP need purposefully to foster knowledge and skills during the transition to adulthood. They should be not only providers of information but also enablers of opportunities for immersion in real-life experiences to prepare for adult life. It is important for young people to have the opportunity to discuss challenges and exchange information with their peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 30 publications
1
23
0
1
Order By: Relevance
“…Other topics which AYAs reported desiring more knowledge on included drugs, alcohol, and other lifestyle related information (Bomba et al, 2017;Burström et al, 2017;Garvey et al, 2014;Lopez et al, 2015;Morsa et al, 2018;Nicholas et al, 2018;Price et al, 2011). AYAs wanted pediatric and adult providers to recognize that emerging adults were a specific developmental group with unique needs (Bomba et al, 2017;Carroll, 2015;Freeman, Stewart, Cunningham, & Gorter, 2018;Garvey et al, 2014;Hilderson et al, 2013;Lopez et al, 2015).…”
Section: Recommendations For Improvements To Transition Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other topics which AYAs reported desiring more knowledge on included drugs, alcohol, and other lifestyle related information (Bomba et al, 2017;Burström et al, 2017;Garvey et al, 2014;Lopez et al, 2015;Morsa et al, 2018;Nicholas et al, 2018;Price et al, 2011). AYAs wanted pediatric and adult providers to recognize that emerging adults were a specific developmental group with unique needs (Bomba et al, 2017;Carroll, 2015;Freeman, Stewart, Cunningham, & Gorter, 2018;Garvey et al, 2014;Hilderson et al, 2013;Lopez et al, 2015).…”
Section: Recommendations For Improvements To Transition Preparationmentioning
confidence: 99%
“…Transition was seen as a challenging time for AYAs, and peers could be a resource (Burström et al, 2017;Lochridge et al, 2013;Lopez et al, 2015;Wright et al, 2016). Peers could provide support and mentorship for life before and after transition (Bomba et al, 2017;Freeman et al, 2018;Garvey et al, 2014;Lopez et al, 2015;Morsa et al, 2018;Porter et al, 2017). Peers could assist AYAs in developing communication skills (Burström et al, 2017).…”
Section: Recommendations For Improvements To Transition Preparationmentioning
confidence: 99%
“…10,25 Similarly, across two age-group related categories ( Most important SMD considerations for Adolescents and Young Adults) , panelists noted priorities related to device aesthetics, as well as future-oriented thinking and planning for transition to college, work, or independent living, which is also consistent with literature describing the importance of transition services and education as young people with CP assume more responsibility for their healthcare and participation. 26,27…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that young people diagnosed with CP do not receive sufficient information prior to transitioning underscoring the need to foster knowledge and improve their skills during the transition period [13]. To overcome these apparent challenges, we need to fully understand the healthcare needs of adults with CP in order to guide the development of adult-focused health services [14].…”
Section: Introductionmentioning
confidence: 99%